In Vitro Evaluation of Gastric Acid and Toothbrushing Effect on the Surface State of Different Types of Composite Resins - Ionuț Tărăboanță; Gabriela Gelețu; Simona Stoleriu; Gianina Iovan; Nicoleta Tofan; Andra Claudia Tărăboanță-Gamen; Andrei Georgescu; Cosmin Gabriel Popa; Sorin Andrian (Medicina, 2022)
Background and Objectives: The aim of this in vitro study was to evaluate the effect of gastric acid associated with the effect of toothbrushing on the surface roughness of different types of composite resin used for direct restorations. Materials and Methods: The materials used in this study were two microhybrid (Filtek Z250, Herculite XRV) and two nanohybrid (Filtek Z550, Herculite XRV Ultra) composite resins. Two hundred and forty cylindrical samples with a height of 2 mm and a diameter of 6 mm were divided into four groups (groups A, B, C and D) corresponding to each tested material (n = 60). Each group was divided in two subgroups: subgroup I—the samples were submersed in hydrochloric acid and immediately submitted to toothbrushing; subgroup II—the samples were submitted only to toothbrushing. The simulation of the acid attack was performed by immersing the samples in a 0.01 M hydrochloric acid solution for 90 min. This procedure was followed immediately by toothbrushing simulation with 10,000 cycles. The acid attack and toothbrushing simulation were performed for two times. The surface roughness evaluation was performed with a Proscan 2100 profilometer. Repeated Measures ANOVA and Bonferroni post-hoc tests were used to perform the statistical analysis. Results: Simulation of one year of toothbrushing associated or not to hydrochloric acid exposure increases the surface roughness of microhybrid and nanohybrid composite resins. Six months of toothbrushing associated to six months of hydrochloric acid exposure increase the surface roughness of nanohybrid composite resins. Conclusions: Microhybrid composite resins surface becomes rougher after toothbrush and acid submersion when comparing to nanohybrid composite resins.